Safety assessment system for food premises - Fauzan, Nur Syafiqah; Makhilan, Nazmi 'Imran (2021)
Foodborne diseases are caused by contamination of food and occur at any stage of the food production, delivery and consumption chain. (WHO, 2015.) The present invention relates to safety assessment system for food premise which is used to manage the compliance check based on Food Act 1983 and Guideline for Grading Systems for Food Premises in Local Authority Create awareness among end users (especially:occupier of food premise) about the importance of food safety and hygiene.